양안 백내장 동시수술에 대한 효용성과 안전성 - 김정희(Jeong Hee Kim), 공석준(Seok Joon Kong), 김재우(Jae Woo Kim), 임태형(Tae Hyung Lim), 최기용(Ki Yong Choi), 조범진(Beom Jin Cho) (Daihan angwa haghoi jabji, 2015)
목적: 양안 백내장 동시수술(immediate sequential bilateral cataract surgery, ISBCS)의 효용성(efficacy) 및 안전성(safety)을 알아보았다. 대상과 방법: 2010년 1월부터 2014년 12월까지 본원에서 ISBCS 및 delayed sequential bilateral cataract surgery (DSBCS)를 시행받은 각 군 70명 140안의 수술 1개월 후 최대교정시력, 구면렌즈 대응치 및 굴절이상을 분석하고 같은 기간 내 본원에서 백내장 수술을 시행 받은 모든 환자를 대상으로 안내염 발생 건수를 조사하였다. 결과: 수술 후 1개월째 최대교정시력(logMAR)은 ISBCS군에서 0.06 ± 0.72, DSBCS군에서 0.09 ± 0.66이었으며 두 군에서 두 번째 수술한 눈의 최대 교정시력(logMAR)은 각각 0.07 ± 0.64, 0.07 ± 0.18이었다. 수술 후 최대 교정시력, 구면렌즈 대응치, 굴절이상 모두에서 두 군 간의 유의한 차이는 없었다. 총 21,140안에서 안내염은 10안(0.05%)에서 발생하였으며 462명, 924안의 ISBCS군에서는 발생하지 않았다. 결론: ISBCS는 적절한 적응증의 환자를 선택하여 경험 많은 술자가 수술을 시행하고, 예방적 항생제를 수술 후 철저히 사용한다면 환자의 만족도를 높이는 안전한 수술 방법으로 생각된다. Purpose: To evaluate the efficacy and safety of immediate sequential bilateral cataract surgery with respect to patient outcomes and complication rates. Methods: From January 2010 to December 2014, we conducted a retrospective study of patients who had immediate sequential bilateral cataract surgery (ISBCS) and delayed sequential bilateral cataract surgery (DSBCS) with an interval of one to two months between the first and the fellow eye operations. The changes in visual acuity, manifest spherical equivalent, and refractive error of 140 eyes of 70 patients of both groups were compared postoperatively at one month. The incidence of endophthalmitis was investigated during the same period. Results: At one month postoperatively, log MAR best corrected visual acuity were measured to be 0.06 ± 0.72 in the ISBCS group and 0.09 ± 0.66 in the DSBCS group, and that of the fellow eyes were 0.07 ± 0.64 and 0.07 ± 0.18, respectively (p = 0.331, p = 0.781, respectively). The postoperative spherical equivalents were -0.18 ± 0.23 D in the ISBCS group and -0.19 ± 0.25 D in the DSCBS group, and that of the fellow eyes were -0.15 ± 0.18 D and -0.16 ± 0.21 D, respectively. There were no significant statistical differences between the two groups (p = 0.835, p = 0.676, respectively). The postoperative refractive error was -0.20 ± 0.21 D in the ISCBS group and -0.18 ± 0.13 D in the DSBCS group, and that of the fellow eyes were -0.14 ± 0.22 D and -0.19 ± 0.22 D, respectively (p = 0.482, p = 0.237, respectively). A total of 21,140 eyes had cataract surgery performed, and only 10 eyes (0.05%) developed endophthalmitis. Endophthalmitis did not occur in the ISBCS group. Conclusions: In experienced hands, with stringent patient selection criteria and with a strict aseptic protocol, ISBCS can safely provide comparable visual outcome and better satisfaction of the patient with good efficacy. KCI Citation Count: 1